5-4(t+1)=t+6

Simple and best practice solution for 5-4(t+1)=t+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-4(t+1)=t+6 equation:


Simplifying
5 + -4(t + 1) = t + 6

Reorder the terms:
5 + -4(1 + t) = t + 6
5 + (1 * -4 + t * -4) = t + 6
5 + (-4 + -4t) = t + 6

Combine like terms: 5 + -4 = 1
1 + -4t = t + 6

Reorder the terms:
1 + -4t = 6 + t

Solving
1 + -4t = 6 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
1 + -4t + -1t = 6 + t + -1t

Combine like terms: -4t + -1t = -5t
1 + -5t = 6 + t + -1t

Combine like terms: t + -1t = 0
1 + -5t = 6 + 0
1 + -5t = 6

Add '-1' to each side of the equation.
1 + -1 + -5t = 6 + -1

Combine like terms: 1 + -1 = 0
0 + -5t = 6 + -1
-5t = 6 + -1

Combine like terms: 6 + -1 = 5
-5t = 5

Divide each side by '-5'.
t = -1

Simplifying
t = -1

See similar equations:

| 5x+76-8=2x-1 | | -2=4(k+8)-3k | | b=3-3/20*10 | | 120=(x+20)+4x | | 3-1/5e=7 | | x+6=8x | | 63+(-18)+12= | | x^2*x=1 | | 25j-163=12 | | 45x+75=255 | | -14=4n+3n | | 2+n=6 | | 1/x^2=x^2 | | 2x(2x+4)=2x+3 | | 9=4m-6-5 | | 4-5y=9-6y | | y=(7-2k)x | | 15-6=9 | | 7/12t-1/4=2y-5/3 | | Q-7=3 | | 4x+(x+20)=120 | | 19+(-19)= | | -10+4(3n+10)=18 | | 4y^2+19y+12= | | -6.5t+15=-9.7t-43.8 | | 3-7y=6-8y | | -64=-8(p+1) | | X(x-48)=180 | | 12+12n=-48 | | -2x+12=0 | | 11/12t-3/4t=5/6 | | -1/7(7y+5) |

Equations solver categories